Are There Common Characteristics among Alcohol Retail Outlets that make them more likely to commonly pass Alcohol Purchase Surveys and commonly fail Alcohol Purchase Surveys? - McCallum, Lindsey (East Carolina University, 2021)
Underage consumption of alcohol is a serious public health issue all across the United States. Identifying the stores and institutes where youth are obtaining alcohol is the most important step towards inhibiting and eliminating underaged drinking in most communities. Alcohol purchase surveys (APS) and alcohol environmental scans (AES) were used to determine common characteristics of alcohol retail outlets that may cause them to commonly pass an alcohol purchase survey experience or commonly fail an alcohol purchase survey experience. Identifying these common characteristics between retail outlets is an important step towards detecting the factors in different communities that increase the probability that an underaged individual can purchase alcohol. APSs are conducted annually for all off-premise alcohol outlets. Environmental scans of the same off-premise alcohol outlets were conducted during the Fall of 2020. Environmental scans were conducted by using a windshield survey method, which involved making observations about an alcohol outlet from a car parked in the outlet’s parking lot. Results indicate that there are common characteristics between all of the outlets that failed their APS 2 or more times within the last 5 years of data collection, such as the identifiable racial/ethnic group that frequent the outlet, the amount of traffic around the outlets, and the type of outlet. Common characteristics were also identified for all of the outlets that passed their APS, meaning they did not fail 2 or more times within the last 5 years. The results from the Environmental scans also show that there are trends between certain types of outlets that influence its likelihood of displaying signs regarding a minimum age to purpose alcohol. This research that involved conducting alcohol purchase surveys and alcohol environmental scans has the potential to greatly decrease the number of outlets who sell alcohol to underaged individuals, as well as identify the factors of an outlet and its surrounding environment that may increase its likelihood to serve the underaged population.
Keywords: Alcohol Purchase Survey; Alcohol Environmental Scan